Análise estática e dinâmica de estruturas reticuladas : ambiente de simulçaão em JAVA - Queiroz, Paulo César de Oliveira (2010)
In this work a static and dynamic elastic analyses of frame structures using the finite element method (FEM) is described. The superstructure is modeled employing six sets of frame structures (plane truss, space truss, plane frame, grilled, space frame and space frame stiffened by shear cores) and specific finite elements are developed for these purposes. According to the specific case, bending effects (Euler-Bernoulli or Timoshenko models), torsional effects (under Saint Venant or Vlasov assumptions) are properly operated and the explicit forms of stiffness and mass matrices and equivalent nodal vector are presented. Special attention is paid to the static soil-structure interaction problem. In this case the superstructure (standard space frame) is modeled by FEM, whereas the soil is assumed to be an elastic half-space and modeled by the boundary element method (BEM). Finally the algebraic systems from both methods are coupled in order to allow the soil-structure interaction analysis. Another focus of this study is to develop a simulation environment (called SAPROMS NET) incorporating mainly the preprocessing and processing steps and both are implemented in object-oriented language Java. Some numerical examples are presented, as well as details of the simulation environment.